Fermentation Time-Dependent Changes in Bioactive Compounds and Physicochemical Properties of Starfruit (Averrhoa carambola L.) Kombucha - Ifah Izzati Harjilah; Ambarwati Ambarwati (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2026)
Background: The rising prevalence of hypertension drives the development of local functional beverages. Starfruit (Averrhoa carambola L.) is a potential kombucha raw material due to its vitamin C and antioxidants, which increase through fermentation. This study analyzes the rarely researched effect of fermentation duration on starfruit kombucha's biochemical traits. Methodology: An experimental Completely Randomized Design (CRD) evaluated 4, 6, and 8-day fermentation durations with two replications. Fermentation occurred at room temperature (20-27°C) using SCOBY (Symbiotic Culture of Bacteria and Yeast). Tested parameters included vitamin C (iodometric titration), antioxidant activity (DPPH), alcohol content (alcoholmeter), and pH. Data were analyzed using descriptive quantitative methods. Findings: Longer fermentation increased vitamin C, antioxidant activity, and alcohol content, but decreased pH due to rising acidity. The 8-day fermentation yielded optimal bioactivity: 167.405 mg/100g vitamin C, 80.630% antioxidant activity, and the lowest pH (4.470). However, its alcohol content reached 0.584%, slightly exceeding the 0.5% non-alcoholic limit. Thus, fermentation duration significantly alters the biochemical profile of starfruit kombucha. While an 8-day fermentation maximizes bioactive compounds, process optimization is needed to reduce alcohol levels to meet food safety standards. Contribution: The novelty of this research lies in assessing starfruit kombucha's biochemical characteristics across varying fermentation durations, an area rarely reported previously